Evaluation of vinpocetine as a therapy in patients with sensorineural hearing loss: A phase II, open-label, single-center study - Ileana Gutiérrez-Farfán; Celia Reyes-Legorreta; Mauricio Solís-Olguín; Efrén Alatorre-Miguel; Antonio Verduzco-Mendoza; Alfredo Durand-Rivera (Elsevier, 2021)
The progressive degeneration of the excitable cells of the ear depends on the sustained excitation of the voltage-sensitive sodium channels, so the negative pharmacological modulation could be a rational therapeutic strategy against the damage of these cells. The objective was to demonstrate the effectiveness of Vinpocetine (VPC), a potent sodium channel blocker, as a treatment for acquired sensorineural hearing loss.A phase II, longitudinal and prospective open clinical study, was conducted over a period of 12 months with patients older than 18 years, to demonstrate the effectiveness of Vinpocetine (VPC) as a treatment for acquired sensorineural hearing loss, using evoked potentials, otoacoustic emissions, audiometry and logoaudiometry, analyzing the results at 6 and 12 months of treatment with Vinpocetine (30 mg/day in 3 doses).It was observed that from 0 to 6 months there was hearing impairment (which was already expected due to the age of the patients). From 6 to 12 months and from 0 to 12 months there were significant differences with a tendency towards improvement, indicating that the aforementioned deterioration not only stopped, but that with the use of vinpocetine, the hearing capacity improved.It is concluded that Vinpocetine helps to stop hearing impairment and even improve hearing.